2005
DOI: 10.1007/s00239-004-0218-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Yeast Proteome to Other Fungal Genomes to Find Core Fungal Genes

Abstract: Abstract. The purpose of this research was to search for evolutionarily conserved fungal sequences to test the hypothesis that fungi have a set of core genes that are not found in other organisms, as these genes may indicate what makes fungi different from other organisms. By comparing 6355 predicted or known yeast (Saccharomyces cerevisiae) genes to the genomes of 13 other fungi using Standalone TBLASTN at an e-value <1E-5, a list of 3340 yeast genes was obtained with homologs present in at least 12 of 14 fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 35 publications
1
40
0
Order By: Relevance
“…Also the number of genes reported to be exclusive to one lineage varied (e.g. 17 genes in the study of Hsiang and Baillie (2005) were not detectable in other lineages, whereas Bowler et al (2008) reported around 1,000 diatom specific core genes). However, most above-mentioned studies were based on genome comparisons.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Also the number of genes reported to be exclusive to one lineage varied (e.g. 17 genes in the study of Hsiang and Baillie (2005) were not detectable in other lineages, whereas Bowler et al (2008) reported around 1,000 diatom specific core genes). However, most above-mentioned studies were based on genome comparisons.…”
Section: Introductionmentioning
confidence: 97%
“…Previous investigations of core genes aimed at various research topics spanning from the identification of the minimal gene set necessarily for cellular life (Gibson et al 2008, Gil et al 2004, Koonin 2003 and the reconstruction of the evolutionary history of a lineage (Bowler et al 2008, Hsiang and Baillie 2005, Armbrust et al 2004) to the identification of group specific core genes as a basis for barcoding approaches (Segata et al 2012) and for the identification of novel features within lineages (Bowler et al 2008). Gil et al (2004) reported a minimal gene set necessary for life for bacteria as low as 250 genes and Koonin (2003) estimated the smallest genomes of free-living organisms to be around 500 genes for bacteria and around 2,000 genes for eukaryotes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By comparing the genomes of the host and of the pathogen, or of the pathogen and a species similar to the pathogen but non-pathogenic, insights can be gained into target sites for antimicrobial activity including novel fungicide target sites. Hsiang and Baillie (2005) found 17 uniquely fungal genes in their analyses of 14 fungal genomes compared with 2 genomes each of plants, animals and bacteria. They pointed out that seven of these 14 genes were already listed in U.S. patents dealing with antifungal drug discovery.…”
Section: Unique Target Sites In Pestsmentioning
confidence: 99%
“…Because the cDNA library was thought to include half of all P. carnii genes, they then estimated the essential eukaryotic core to be approximately 400 genes. Hsiang and Baillie (2005) searched for homologs of Saccharmoyces cerevisiae genes among 13 other fungal species. They found that out of the 6355 putative Saccharomyces cerevisiae genes, 3340 were present in at least 12 other fungal genomes (at e-value < 10 -5 ).…”
Section: Fungal Comparative Genomics -Essential Fungal Genesmentioning
confidence: 99%